Effects of Simultaneous Downregulation of PHD1 and Keap1 on Prevention and Reversal of Liver Fibrosis in Mice - Liu, Jing; Li, Wencai; Limbu, Manoj H.; Li, Yiping; Wang, Zhi; Cheng, Zhengyuan; Zhang, Xiaoyi; Chen, Pingsheng (Frontiers in Pharmacology, 2018)
Background and Aims: To investigate whether double-knockdown of PHD1 and Keap1 in mice could enhance the resolution of carbon tetrachloride (CCl4)-induced liver fibrosis. Methods: The liver fibrosis model of mice was established by intraperitoneal injection of 25% CCl4 in olive oil (4ul/g) twice a week for 8 weeks. PHD1shRNA and Keap1shRNA eukaryotic expression plasmids were simultaneously administered from the beginning of the first week to the fourth week (preventive group) or from the fifth week to eighth week of CCl4 injection (therapeutic group) via hydrodynamic-based tail vein injection. Successful transfection was confirmed with the expression of red fluorescent protein (RFP) and green fluorescent protein (GFP) in hepatocytes. Western blot was used for determining the expression of PHD1 and Keap1, HE, Sirius red and Masson staining for evaluating the histopathological stages of fibrosis. Immunohistochemical technique were applied to evaluate the expression of -SMA. Results: The fluorescence of red and green were observed mainly in hepatocytes, and downregulation of PHD1 and Keap1 expression in liver was detected by western blot. Meanwhile, Double-knockdown of PHD1 and Keap1 in mice alleviated liver fibrosis, and the effect was further enhanced especially in the preventive group. Immunocytochemical staining showed decreased expression of -SMA when both PHD1 and Keap1 were knockdown. Conclusions: Downregulation of PHD1 and Keap1 expression in the liver could be achieved via hydrodynamic injection of PHD1shRNA and Keap1shRNA, thereby,preventing liver fibrosis.